Participant interaction models and roles in a computer supported collaborative learning (CSCL) environment: a Malaysian case study - Daniel, E.G.S. (2001)
In this paper, three models of participant interactions in a Web-based instruction courses were identified among a diverse group of seven adult learners in a Course-On-Line, Masters of Instructional Technology Program at the University of Malaya (Malaysia). The three models were named the cyclical model, the hierarchical model, and the parallel model. The cyclical model depicts the interactions of the computer, instructor and the learner as in a cycle. The hierarchical model views the instructor and the computer as the participants in a level higher than the learner. The parallel model sees the learner and the instructor progressing parallel to one another mediated by the computer. The roles of the participants in the computer-supported collaborative learning (CSCL) class as perceived by the learners are also discussed. The paper concludes: it can be said that this case study has uncovered some insights into how a diverse group of adult learners perceived interactions between participants in a CSCL environment and how they utilized this dynamic interaction to construct and create knowledge out of a colossal amount of information.